Evaluation of Ki-67 Antigen and Protein P53 Expression in Orthokratinized and Parakratinized Odontogenic Keratocyst - F. Baghaei; M. Eslami; D. Sadri (Tehran University of Medical Sciences, 2004)
Statement of Problem: Odontogenic Keratocysts (OKC) make up 10-12% of all developmental cysts with dental origin. OKCs are classified into parakeratotic and orthokeratotic types, with completely different clinical features. In order to investigate biological behavior of OKCs, an immunohistochemical study was designed, using Ki-67 antigen as proliferation marker and P53 protein as tumor suppressor gene. Purposes: The aim of the present study was to investigate the expression of P53 and Ki-67 markers in two types of OKCs and to determine their relationship with the biological behaviour of OKC. Materials and Methods: A total of 20 OKCs (parakeratotic n=10, orthokeratotic n=10) were stained immunohistochemically for Ki-67 and P53 protein by Biotin - Streptavidine method. Then, slides were studied quantitatively through optical lense (magnification=X10) and the number of positively stained cells was counted/mm BM. Results: The average number of Positively stained cells for Ki-67 were 62.30±11.96 cells/mm BM in parakeratotic, and 29.90±4.90 cells/mmBM in orthokeratotic OKCs (P